The Institution of Science and the Science of Institutions
XII, 227 p. 4 illus.
Keywords: The present anthology, edited by Marcel Herbst, is partially based on a conference, held in 2009, to reflect on the legacy of Ben-David, and contains a selection of substantially revised papers, plus four contributions specifically written for this volume. The book focuses on three major lines of Ben-David’s research, namely “Center and Periphery” (Part I), “Role and Ethos” (Part II), and “Organization and Growth” (Part III). In addition, comprehensive introductory (“Prologue”) and concluding chapters (“Epilogue”, Part IV) by Marcel Herbst are provided. The volume addresses the following disciplines: higher education, history and sociology of science, philosophy of science, history of medicine, public administration, policy studies, Jewish studies, and economics. The anthology is one of two new publications on Joseph Ben-David after the special Minerva edition Vol. 25, Numbers 1–2, March 1987, and Gad Freudenthal’s collection of Ben-David’s writings [1991]. The text can be used in graduate studies, it addresses higher education professionals or public officials, and serves as a gateway to researchers in the field of higher education, science studies, or policy sciences.